Processing, preservation, and value addition of indigenous food crops in West Africa - Amissah, Joris Gerald Niilante; Adjei, Maame Yaakwaah Blay; Amissah, Jacqueline Naalamle; Asem, Freda Elikplim; Kolog, Jude Dokbila (Frontiers in Sustainable Food Systems, 2025)
This review paper examines the processing and preservation methods of indigenous food crops in West Africa with a focus on their importance for nutrition security as part of the strategies to mitigate the adverse effects of climate change. Indigenous crops are nutritious, climate resilient and important in the diets of local communities. However, they tend to be underutilized when addressing national and regional food security needs. This paper explores the use of indigenous traditional food processing and preservation methods as well as the use of modern and innovative technologies for the reduction of postharvest losses, maintenance of nutritional quality, value addition and increased shelf-life, to ensure the year-round availability and affordability of these food crops. The paper also demonstrates how the integration of indigenous traditional methodologies with more modern processing techniques can increase the utilization of indigenous food crops with improved livelihoods for smallholder farmers and additional benefits for national and regional food security. Findings show that traditional methods remain vital but are faced with hygiene and labor challenges, while modern technologies improve efficiency but are costly. Integrated approaches enhance food safety, nutrient retention, and market access, empowering women and smallholder farmers. The paper recommends gender-responsive policies, decentralized processing hubs, and participatory innovation to scale integrated methods for resilient food systems.